Data from: Single nucleotide polymorphism (SNP) variation of wolves (Canis lupus) in Southeast Alaska and comparison with wolves, dogs, and coyotes in North America - Medrano, Juan F.; Cronin, Matthew A.; Cánovas, Angela; Oberbauer, Anita M.; Bannasch, Danika L. (2014)
There is considerable interest in the genetics of wolves (Canis lupus) because of their close relationship to domestic dogs (C. familiaris) and the need for informed conservation and management. This includes wolf populations in Southeast Alaska for which we determined genotypes of 305 wolves at 173662 single nucleotide polymorphism (SNP) loci. After removal of invariant and linked SNP, 123801 SNP were used to quantify genetic differentiation of wolves in Southeast Alaska and wolves, coyotes (C. latrans), and dogs from other areas in North America. There is differentiation of SNP allele frequencies between the species (wolves, coyotes, and dogs), although differentiation is relatively low between some wolf and coyote populations. There are varying levels of differentiation among populations of wolves, including low differentiation of wolves in interior Alaska, British Columbia, and the northern US Rocky Mountains. There is considerable differentiation of SNP allele frequencies of wolves in Southeast Alaska from wolves in other areas. However, wolves in Southeast Alaska are not a genetically homogeneous group and there are comparable levels of genetic differentiation among areas within Southeast Alaska and between Southeast Alaska and other geographic areas. SNP variation and other genetic data are discussed regarding taxonomy and management.